2022
DOI: 10.3390/biomedicines10030558
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Significance of Elevated IgG4 in Rheumatoid Arthritis: A Systematic Review

Abstract: Immunoglobulin (Ig)G4 is a unique protein molecule and its role in autoimmune diseases remains elusive and controversial. Accumulating evidence suggests a pathogenic role of IgG4 in rheumatoid arthritis (RA). Rheumatoid factors (RF) in RA can recognize the Fc domains of IgG4 to form RF-IgG4 immune complexes that may activate the complement system leading to synovial injury. The aim of this article was to systematically review the literature from the past 2 decades to determine the frequency of elevated IgG4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(102 reference statements)
1
8
0
Order By: Relevance
“…Given the fact that IgG4 are generally relatively poor activators of complement and Fcγ receptors (FcγRs) [51], the absence of a correlation in ACPA seems plausible. The finding that total IgG4 levels correlated with mentioned inflammatory markers is supported by a significant but relatively weak correlation of these two factors in a recent meta-study and is worth further investigation [53]. Next to subclasses, we assessed IgG sequence variations (allotypes) and monitored their relative abundance per subclass.…”
Section: Discussionmentioning
confidence: 93%
“…Given the fact that IgG4 are generally relatively poor activators of complement and Fcγ receptors (FcγRs) [51], the absence of a correlation in ACPA seems plausible. The finding that total IgG4 levels correlated with mentioned inflammatory markers is supported by a significant but relatively weak correlation of these two factors in a recent meta-study and is worth further investigation [53]. Next to subclasses, we assessed IgG sequence variations (allotypes) and monitored their relative abundance per subclass.…”
Section: Discussionmentioning
confidence: 93%
“…However, in some RA models, IL‐4‐deficient mice were protected from severe disease. In addition, IL‐4 also activates B cells and induces isotype switching to IgG4, which dominates autoantibodies found in RA sera 178 . Therefore, the role of IL‐4 in RA and other autoimmune diseases, like systemic lupus erythematosus (SLE), is complex and depends upon genetic background, the type of eliciting antigen, and the relative role of autoantibodies in pathogenesis.…”
Section: Diseases With An Il‐4‐/il‐13‐dominant Cytokine Profilementioning
confidence: 99%
“…In addition, IL-4 also activates B cells and induces isotype switching to IgG4, which dominates autoantibodies found in RA sera. 178 Therefore, the role of IL-4 in RA and other autoimmune diseases, like systemic lupus erythematosus (SLE), is complex and depends upon genetic background, the type of eliciting antigen, and the relative role of autoantibodies in pathogenesis. Further delineation of IL-4/-13 in autoimmune disorders will inform the design and validation of clinical therapies to treat these diseases.…”
Section: Functionalresponsesmentioning
confidence: 99%
“…Blocking IL6 by tocilizumab has been shown to reduce IgG4 ACPA antibodies, but not IgG1 ACPA antibodies, indicating the potential in uence of IL-6 on the production of IgG4 anti-CCP antibodies in RA. (9) Sakthiswary et al (10) recently completed a systematic review of nineteen studies where serum IgG4 in RA was assessed. They showed that elevated IgG4 level was positively correlated with increased disease activity (measured by DAS28-ESR ) and in ammatory markers.…”
Section: Igg4rd With Autoimmune Overlapmentioning
confidence: 99%